The Effect of Legal - Ethical And Psychological Factors In Reducing Accounting Manipulations: A Field Study - Muhammad Ali Jaafar; Alaa Mohsin Muttlaq Al-Daamy (Technium Business and Management, 2024)
The study aimed to elucidate the extent of accountants’ adherence to legal and ethical factors, understand the psychological state of the auditor, explore the impact of regulations governing the auditing profession, and delineate the effect of psychological and ethical factors on the auditor’s behavior. The study also sought to gather opinions from auditors, academics, and educators at the University of Baghdad regarding legal, ethical, and psychological factors within the profession. The study found significant correlations between legal, ethical, and psychological factors, and accounting manipulations. There was a statistically significant relationship between legal factors and accounting manipulations, with a correlation coefficient of (0.383) at a significance level of less than (0.01). Similarly, a significant relationship was found between ethical factors and accounting manipulations, with a correlation coefficient of (0.416) at a significance level of less than (0.01). Moreover, a significant relationship was established between psychological factors and accounting manipulations, with a correlation coefficient of (0.659) at a significance level of less than (0.01). The study recommends providing objective solutions to contribute to identifying the reasons for committing manipulation within organizations. It emphasizes the need to implement financial statement analysis techniques as a means of detecting manipulation and underscores the importance of legal actions (civil and criminal) related to filing claims in court, and preserving and protecting evidence. Additionally, auditors should act impartially, separating personal interests from their supervisory role.